Self-administered versus provider-directed sampling in the Anishinaabek Cervical Cancer Screening Study (ACCSS): a qualitative investigation with Canadian First Nations women. Issue 8 (1st September 2017) - Zehbe, Ingeborg; Wakewich, Pamela; King, Amy-Dee; Morrisseau, Kyla; Tuck, Candace
Abstract : Background: While (Pap)anicolaou screening has helped to decrease cervical cancer incidence in Canada, First Nations women continue to have a higher burden and mortality relative to mainstream populations. Many First Nations women may feel uncomfortable with the invasiveness of this test, contributing to this statistic. Implemented from 2009 to 2015 in 10 Northwest Ontario First Nations communities, the Anishinaabek Cervical Cancer Screening Study (ACCSS) uniquely addressed this Indigenous health inequity through a mixed methods approach. Objective: Our goal was to offer an alternative test which the women could do themselves: human papillomavirus (HPV) testing based on self-sampling. We investigated whether First Nations women preferred HPV self-sampling over healthcare provider (HCP)-administered Pap screening. Methods: Participatory action researchinformed by the ethical space concept has guided all stages of the ACCSS. We conducted qualitative interviews with 16 HCPs and 8 focus group discussions with 69 female community members followed by a cluster-randomised controlled trial (RCT). Here, we draw on the qualitative field data and an end-of-study community update gathering to disseminate and contextualise research findings. Informant data were evaluated using thematic analysis. Results: We discuss factors influencing participants' strong preference for HPV self-sampling over physician-conducted Pap screening. Key arguments included enhanced accessibility and more personal control, less physical and emotional discomfort and fewer concerns regarding privacy of test results. For future implementation of HPV self-sampling, study participants emphasised the need for more culturally sensitive education addressed to community members of all genders, starting at school, clarifying that HPV causes cervical cancer. Further, HPV infection should be de-stigmatised by accentuating that it affects men and women alike. Conclusion: Here we show that self-sampling in conjunction with community engagement and culturally sensitive education and could be a viable option for underscreened Canadian First Nations women. These informant data echo our previous RCT results.